1994
DOI: 10.1002/mrm.1910320108
|View full text |Cite
|
Sign up to set email alerts
|

A novel saturation transfer contrast method for 3D time‐of‐flight magnetic resonance angiography: A slice‐selective off‐resonance sinc pulse (SORS) technique

Abstract: Saturation transfer contrast (STC) techniques have been employed to decrease the signal intensity of observed water by saturating a broad proton component. The STC pulse, generally spatially nonselective, reduces the signal of brain background tissues as well as inflowing blood in 3D time-of-flight (TOF) angiography. We present a novel technique, a slice-selective off-resonance sinc pulse (SORS), which is employed to enhance inflowing blood and to suppress the signal of stationary background tissues. The STC e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Not only the signal contrast ratio (blood/background), but also the reduction of the signal intensity of the brain background was largest when using the SORS method. 6 We used an MTC pulse of 5009because in our clinical MRA protocol, although an MTC pulse of 3609was applied and SNc was often identiˆed, we felt that it was not enough to visualize the LC by this protocol. Edelman and colleagues reported that larger MTC pulse permitted substantial improvement in small vessel conspicuity in time-of‰ight MR angiography, 11 so we selected the larger 5009pulse.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only the signal contrast ratio (blood/background), but also the reduction of the signal intensity of the brain background was largest when using the SORS method. 6 We used an MTC pulse of 5009because in our clinical MRA protocol, although an MTC pulse of 3609was applied and SNc was often identiˆed, we felt that it was not enough to visualize the LC by this protocol. Edelman and colleagues reported that larger MTC pulse permitted substantial improvement in small vessel conspicuity in time-of‰ight MR angiography, 11 so we selected the larger 5009pulse.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…We consider 2 possible reasons for ourˆndings. First, we selected a SORS-STC pulse 6 that generated MTC, which enhances in‰owing blood and suppresses the signals of stationary background tissues and veins by applying a slice-selective pulse above the in‰ow-ing blood and maintaining the MTC on the stationary background. In the present study, there was an apparent diŠerence between images taken with and without SORS-STC.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging parameters of TOF-MRA were as follows: TR/TE ϭ 30/6.8 msec, flip angle ϭ 20°, field of view ϭ 180 ϫ 180mm, matrix size ϭ 512 ϫ 512, partition thickness/gap ϭ 1/0 mm, pixel bandwidth ϭ 122 Hz. Magnetization transfer technique was used for suppress background signal on the TOF-MRA (18).…”
Section: Methodsmentioning
confidence: 99%
“…We did not use MTC pulses 12 in the sequence because MTC reduced the CNR of the blood vessels in the second echo. The reduction of TR shortened acquisition time.…”
mentioning
confidence: 99%